Regulation of Pituitary Cocaine- and Amphetamine-Regulated Transcript Expression and Secretion by Hypothalamic Gonadotropin-Releasing Hormone in Chickens - Mo, Chunheng; Lv, Can; Huang, Long; Li, Zhengyang; Zhang, Jiannan; Li, Juan; Wang, Yajun (Frontiers in Physiology, 2019)
There is increasing evidence that cocaine- and amphetamine-regulated transcript (CART) peptide is abundantly expressed in the anterior pituitary of birds and mammals, suggesting that CART peptide may be a novel pituitary hormone and its expression and secretion is likely controlled by the hypothalamic factor(s). To substantiate this hypothesis, using chicken as an animal model, we examined the effects of gonadotropin-releasing hormone (GnRH) on pituitary CART secretion and expression and investigated whether GnRH could modulate plasma CART levels. The results showed that: 1) GnRH (GnRH1 and GnRH2) could potently stimulate CART peptide secretion in intact pituitaries incubated in vitro, as detected by Western blot; 2) GnRH could also stimulate CART mRNA expression in cultured pituitary cells, as revealed by qPCR assay; 3) GnRH actions on pituitary CART expression and secretion are likely mediated by GnRH receptor coupled to the intracellular Ca2+, MEK/ERK and cAMP/PKA signaling pathways; 4) plasma CART levels are high in chickens at various developmental stages (1.2-3.5 ng/mL) and show an increasing trend towards sexual maturity, as detected by ELISA. Moreover, plasma CART levels could be significantly induced by intraperitoneal administration of GnRH in chicks. Taken together, our data provides the first collective evidence that CART peptide is a novel pituitary hormone and its expression and secretion is tightly controlled by hypothalamic GnRH, thus likely being an active player in the hypothalamic-pituitary-gonadal (HPG) axis.